2020
DOI: 10.1177/2058738420910005
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Typhae pollen polysaccharides protect hypoxia-induced PC12 cell injury via regulation of miR-34a/SIRT1

Abstract: This current research was performed to investigate the role of typhae pollen polysaccharides (TPP) in hypoxia-treated PC12 cell which was an in vitro cell model of cerebral ischemia. Hypoxia-treated cells were treated with TPP for 12 h. Cell viability and apoptosis were detected by 3-(4,5-dimethylthiazol-2-yl)-2 5-diphenyl-2H-tetrazolium bromide (MTT) assay and flow cytometry, respectively. Cell apoptotic proteins and PI3K/AKT and Ras/Raf/MEK/ERK signal pathway–associated proteins were also examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It was observed that in the two pancreatic cancer cell lines transfected with db34a, the expression levels of bFGF and CCL5 were significantly increased. miR-34a-5p expression is known to be increased by the activation of the PI3K signaling pathway (51) and, notably, mir-34a-5p has been shown to suppress the PI3K signaling pathway (52)(53)(54)(55)(56). These contradictory observations indicates the possibility of the existence of a tight regulatory apparatus that is not yet clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that in the two pancreatic cancer cell lines transfected with db34a, the expression levels of bFGF and CCL5 were significantly increased. miR-34a-5p expression is known to be increased by the activation of the PI3K signaling pathway (51) and, notably, mir-34a-5p has been shown to suppress the PI3K signaling pathway (52)(53)(54)(55)(56). These contradictory observations indicates the possibility of the existence of a tight regulatory apparatus that is not yet clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Rat pheochromocytoma PC12 has the general characteristics of neuroendocrine cells and is broadly used in neurophysiological research (Wang et al, 2020b). Hence, PC12 cells were subjected to oxygen-glucose deprivation/reoxygenation (OGD/R) to mimic I/R in vitro (Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%